Aggressive Small Cell Carcinoma of the Ovary, Hypercalcemic Type With Hypercalcemia in Pregnancy, Treated With Conservative Surgery and Chemotherapy. Issue 8 (1st November 2009) - Mccormick, Timothy Chad; Muffly, Tyler; Lu, George; Shoup, Brenda
Abstract : Background: Small cell carcinoma of the ovary, hypercalcemic type is a rare and aggressive malignancy found in reproductive-age women. Case: We report a 22-year-old pregnant woman found to have symptomatic paraneoplastic hypercalcemia associated with small cell carcinoma of the ovary, hypercalcemic type. She was primarily treated with conservative surgery and chemotherapy secondary to desired pregnancy. She died of the disease 10 months from primary diagnosis. Conclusions: Small cell carcinoma of the ovary, hypercalcemic type is a very aggressive type of ovarian malignancy with a poor prognosis.